OPEN SOURCE SOFTWARE IN HEALTH INFORMATION SYSTEMS: OPPORTUNITIES AND CHALLENGES - Twaakyondo, Hashim M.; Lungo, Juma H. (Tanzania Journal of Engineering and Technology, 2018)
The paper presents results of a study seeking to identify constraining and motivating factors associated with the adoption and use of Free Open Source Software to computerise health Information Systems in a developing country. The study approach is interpretive research to case study with a triangulation of several qualitative data collection methods such as interviews, group discussions and document analysis. The findings indicate that using open source software has advantages and disadvantages. The advantages are low entry cost to adopting software, possibilities of software localization, avoiding being hostage of proprietary software and foster knowledge acquisition among software developers. The disadvantages are the need for constant internet access, high switching costs, and lack of human resources especially IT professionals to maintain the software since users get more rights in using and maintaining the system. The study concludes that because of the dynamics in health information systems, open source is appropriate.